EFFECT OF TAX AVOIDANCE, TAX RISK, AUDIT TENURE, ON FIRM VALUE: ECONOMICS - Dewi, RR Dewi; Sri Hartono; Endang Masitoh (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research aims to examine the influence of tax avoidance, tax risk, audit tenure and financial performance on firm value. The population in this research is 147 manufacturing companies listed on the IDX in the 2019-2023 period. The sampling technique uses purposive sampling. The total data that can be processed is 199. The result is that tax avoidance and tax risk have no effect on firm value. Different results on financial performance and audit tenure which influence firm value. Tax risk is still a new thing for research in Indonesia, so many companies pay less attention because they already carry out tax planning and tax management and manage tax risk management.